TINJAUAN LITERATUR SISTEMATIS: ADOPSI PENGGUNAAN MS TEAMS (PANDANGAN PENGARUH SOSIAL UTAUT MODEL) - Purba, Yuni Kasih; Yoseppin, Graciella; Irwansyah (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study analyzes the social influence on the adoption of Microsoft Teams using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. The method employed is a Systematic Literature Review (SLR), examining 51 relevant articles that discuss social influence and technology adoption. The results show that social support, interpersonal communication, and network size significantly affect an individual's decision to use Microsoft Teams. The article selection process follows the PRISMA methodology, with articles indexed in Q1 and Q2 Scopus journals. The findings indicate that social influences, such as recommendations from friends or colleagues, can enhance an individual's intention to adopt technology. These results provide guidance for policymakers to leverage social influence in promoting the adoption of collaborative technologies, contributing to productivity and collaboration in the education and economic sectors.